AB0429 Pure Red Cell Aplasia in Patients from SLE Registry from The spanish Society of Rheumatology (RELESSER). (15th July 2016) - Lois-Iglesias, A.; Rúa-Figueroa, I.; Erausquin, C.; Grados, D.; Olivé, A.; Quevedo, V.; Alegre, J.; Calvo, J.; Lόpez-Longo, F.; Galindo, M.; deToro, F.; Mouriño, C.; et al.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune systemic rheumatic disease that, in our area, presents hematologic manifestations in approximately 70% of cases 1 . Some of them are very rare, there are no large series whose analysis could provide relevant information. Objectives: To study the characteristics of patients with Pure Red Cell Aplasia (PRCA) in a large sample of SLE patients. Methods: SLE patients from RELESSER database were studied. We analysed the clinical and analytical SLE manifestations at 12 different domains (mucocutaneous, renal, musculoskeletal, constitutional, haematologic, vascular, cardiac, respiratory, neuropsychiatric, gastrointestinal, ophthalmic and serological) before, during and after PRCA diagnosis and until the last available assessment. We also studied activity (SELENA-SLEDAI) and damage (SLICC/ACR DI)indices at each of those times. We evaluated the treatment received, PRCA recurrences and the number of deaths by this entity. Results: 3, 656 patients from 45Rheumatology Units across Spain were studied. 5 cases of PRCA were found (<0.5%of total) There were not viral infections in relation with the PRCA. All patients had a good response to treatment, reaching complete remission without relapses or deaths. The mean number of treatment lines (± SD)that were necessary was 2.2 (±1.01)and the mean (± SD)number of treatments used was 2.8 (±1.92). Except for the patient diagnosed with PRCA before SLE, all of them received glucocorticoids as initial treatment. Of these 4patients only 1achieved complete remission without requiring immunosuppressive therapy. The following table shows the characteristics of each patient: Conclusions: PRCA is a very rare cause of anemia in SLE. In most cases it appears several years after the diagnosis of SLE. It is a serious manifestation but in our series, with a proper management showed a favourable response. References: Pego-Reigosa JM et al. Analysis of disease activity and response to treatment in a large Spanish cohort of patients with systemic lupus erythematosus. Lupus 2015;24:720–9. Disclosure of Interest: A. Lois-Iglesias: None declared, I. Rúa-Figueroa: None declared, C. Erausquin: None declared, D. Grados: None declared, A. Olivé: None declared, V. Quevedo: None declared, J. Alegre: None declared, J. Calvo: None declared, F. Lόpez-Longo: None declared, M. Galindo: None declared, F. deToro: None declared, C. Mouriño: None declared, J. Pego-Reigosa Grant/research support from: Work supported by Spanish Society of Rheumatology, FIS/ISCIII (PI11/02857), BIOCAPS from the EU 7th Framework Programme/REGPOT-2012–2013.1 (316265), GSK, Roche, Novartis, UCB.